The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.17826/cutf.61415
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C-E ve Monosodyum Glutamata Bağlı Ovaryan Toksisite

Abstract: Purpose: Our study aimed to investigate the combinatorial effect of vitamin C and E on oxidative stress, the number of folicles, and hormonal level in female rats orally exposed to monosodium glutamate (MSG). Materials and Methods:Female, twelve weeks old Wistar rats ingested with of MSG at dose 140 mg/200 gram body weight (bw) with or without combination of vitamin C and E. Twenty five rats were divided into five group (n = 5 each), control group, MSG-treatment group, MSG-treatment + 0.2 mg/g bw vitamin C + 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…C and E protected MSG-induced ovarian damage [14]. On the other hand, Group V's results showed an increase, which was ascribed to the vitamins' synergy, which has been linked to a number of metabolic processes.…”
Section: Groupsmentioning
confidence: 84%
“…C and E protected MSG-induced ovarian damage [14]. On the other hand, Group V's results showed an increase, which was ascribed to the vitamins' synergy, which has been linked to a number of metabolic processes.…”
Section: Groupsmentioning
confidence: 84%
“…These studies revealed that MSG causes cytotoxicity [ 12 , 13 ] and oxidative damage in the liver, kidney, and various tissues [ 14 , 15 , 16 , 17 , 18 ] and increased the risk of certain cancers [ 16 ]. MSG may adversely affect immune system organs [ 13 , 18 , 19 ], the testes [ 20 , 21 , 22 ], ovarium [ 23 , 24 , 25 , 26 , 27 ], pancreas [ 28 ], spleen [ 29 , 30 , 31 ], liver [ 15 , 32 , 33 ], and cardiac tissue [ 2 ]. It has been reported that the incidence of certain diseases, such as obesity [ 34 , 35 ], diabetes, and Alzheimer’s is increased in people who consume foods with added MSG [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%